Relational leadership in education : a phenomenon of inquiry and practice - Giles, David L. (New York, NY : Routledge, Taylor & Francis Group, 2019)
'Relational Leadership in Education considers'relational leadership' within the context of education, critiquing the current ideological'context' and contemporary understandings of its influence. Employing a phenomenological approach, this book explores the relational nature of education, relational leadership, and the organisational culture to provide a more sophisticated exploration of practice-based wisdom. It offers an extensive range of activities for further thinking on the experiential nature of relational leadership, grouped around a number of themes' --
The ideological context of educational relationships -- Contemporary understandings of relationships & leadership -- The phenomenology of relationships -- Relationships : the essence of leadership -- Relational leadership -- Relational sensibilities -- Ethical leadership -- Intentional engagement : practices and strategies for enhancing relationships -- The relational nature of organizational culture -- Relational approaches to professional development and learning -- Embedding the phenomenological nature of relationships and leadership within postgraduate programmes for principals and educational leaders -- Relationships in everyday teaching -- Looking back -- Looking forward.
Keywords: Educational leadership; Educators -- Professional relationships; Teachers -- Professional relationships; School administrators -- Professional relationships; Relational leadership